O papel da reserva cognitiva na infeção pelo VIH - Ana Isabel Pestana Lopes (2020)
Introduction: Is is estimated that 50% of people living with HIV suffer from some sort of HIV-associated neurocognitive disorder (HAND), with a growing number of HIV-infected who are over the age of 50. Despite combined neurological risk of aging and HIV, some individuals fail to show notable impairment. The cognitive reserve theory appears to explain differential susceptibility of cognitive abilities to pathology or insult. This review aims to answer the following question: what is the role of cognitive reserve in HIV infection? Methods: The acquisition of the bibliographic information was conducted through a research on the Scopus platform, starting from the following combination of terms: cognitive reserve, cognitive dysfunction and HIV. Studies obtained in the last 10 years were analysed, corresponding to investigations mainly focused on the relationship between cognitive reserve, cognitive dysfunction and HIV. Results: Most studies corroborate the neuroprotective effect of having higher cognitive reserve, commanding the negative effects on cognition due to HIV, in all stages of the infection. Accelerated/premature aging associated with HIV infection also seems to be buffered, in older HIV-infected people with higher cognitive reserve, by hyperactivation of adjacent cerebral areas in charge of performing a task. Discussion: Cognitive reserve seems to mediate the negative effects of HIV on cognition, preserving neuropsychological and real-life function in people with higher cognitive reserve, irrespective of their HIV disease stage and age. Conclusion: Cognitive reserve may be an important concept in the context of rehabilitation as a prognostic construct and as a target of intervention in cognitive impairment associated with HIV infection.